2016
DOI: 10.1371/journal.pone.0166052
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hypoxia on Drug Resistance and Growth Characteristics of Mycobacterium tuberculosis Clinical Isolates

Abstract: Mycobacterium tuberculosis (MTB) is a specific aerobic bacterium, but can survive under hypoxic conditions, such as those in lung cheese necrosis, granulomas, or macrophages. It is not clear whether the drug sensitivity and growth characteristics of MTB under hypoxic conditions are different from those under aerobic conditions. In this study, we examined the drug resistance and growth characteristics of MTB clinical isolates by a large sample of in vitro drug susceptibility tests, using an automatic growth ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Mycobacteria were grown to mid-log phase in 7H9 broth with 10% ADC, 0.05% Tween 80, and antibiotics, as required. Growth curves for each strain were determined using a Bioscreen C Growth Curve Instrument (Labsystems Oy, Helsinki, Finland) and a honeycomb plate with 100 wells (Labsystems Oy) 48 . Briefly, 200 μL of each bacterial suspension, adjusted to a similar density, was added to each well and cultured with shaking at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Mycobacteria were grown to mid-log phase in 7H9 broth with 10% ADC, 0.05% Tween 80, and antibiotics, as required. Growth curves for each strain were determined using a Bioscreen C Growth Curve Instrument (Labsystems Oy, Helsinki, Finland) and a honeycomb plate with 100 wells (Labsystems Oy) 48 . Briefly, 200 μL of each bacterial suspension, adjusted to a similar density, was added to each well and cultured with shaking at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The implications of hypoxic condition in caseum are significant because an in vitro model that gradually depletes oxygen and then maintains low oxygen tension (Wayne model) triggers an adaptive dormancy response in M. tuberculosis (65,116). In this model, M. tuberculosis arrests replication, decreases intracellular ATP levels (117), represses an array of cellular functions, including protein and DNA synthesis (118), and develops phenotypic resistance to most TB-active antibiotics (119,120). At the molecular level, the dormancy response to hypoxia is mediated by the transcription factor Rv3133c, or DosR (for dormancy survival regulator) (87,118,121).…”
Section: Hypoxiamentioning
confidence: 99%
“…The transporter Rv0194 has two TMDs and two NBDs encoded by a single gene (Table 3). Disruption of the rv0194 gene promotes the in vitro growth of H37Rv [46], although proteomics studies have shown that it is a non-essential gene [47,125]. On the other hand, rv0194 is significantly upregulated under hypoxic conditions compared to under aerobic conditions [126].…”
Section: Drug Efflux and Resistance In M Tuberculosismentioning
confidence: 99%